The Prevalence of Fragility Fractures in a Population of a Region of Southern Italy Affected by Thyroid Disorders. (11th October 2016) - Maccagnano, Giuseppe; Notarnicola, Angela; Pesce, Vito; Mudoni, Simona; Tafuri, Silvio; Moretti, Biagio
Abstract : In the literature there is no clear evidence of a relationship between thyropathies and fragility fractures. The aim of our study is to define the prevalence of thyroid disease in a study sample made up of subjects with fragility fractures and from the same geographical area. We retrospectively studied the "hospital discharge records" (HDR) in the Apulian Database for the period 2008–2013 in order to identify all those patients with fragility fractures that required hospitalization. After detecting the prevalent population, we identified the patients affected by thyroid disease. We observed that, between 2008 and 2013 in Apulia, 16, 636 patients were affected by hyperthyroidism. In the same period there were 92, 341 subjects with hypothyroidism. The incidence of fragility fractures was 4.5% in the population with hyperthyroidism. As regards the population with hypothyroidism, the incidence of fragility fractures was 3.7%. Furthermore, we assessed the statistical connection between thyroid disease and fragility fractures revealing a higher incidence in patients with hyperthyroidism and clinical hypothyroidism.